(untitled) (International Journal of Geoscience, Engineering and Technology, 2020)
At the moment when new sketches of South American phytogeographic regions and morphoclimatic domains are frequently produced, the relevance of a review of the origin and evolution process of one of the most important geosystems of brazilian biodiversity is imminent: the Fields of Serra Espinhaço. This is because despite being within the most complex and biodiverse are also among the most endangered on the planet, either due to degrading activities in their region of occurrence, or the impact of climate change on the dynamics of functional of the ecosystem. In this sense, the objective of this paper is to review the process of origin and phytogeographic evolution of the Serra do Espinhaço Rupestrian Fields, in order to understand how these ecosystems emerged in the context of the Quaternary period, as they were established during the climate changes of the Holocene and Pleistocene, what are the current vegetation characteristics that can contribute to the understanding of this paleoecological dynamics and consequently of the evolutionary history of the Rupestrian Fields species. From the reading of the available works about the Rupestres Fields it is possible to assume that they represent a relictual vegetation, whose process of establishment took place throughout the Quaternary, however one cannot also rule out the influence of even older events in the process of origin of the Rupestrian Fields. Such complexity in geosystemic dynamics presupposes complex conservation models of this ecosystem, considering the contribution of each piece of this complex puzzle to define the best strategies for maintaining the functional balance of vegetation.